2007
DOI: 10.1063/1.2717562
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization process and amorphous state stability of Si-Sb-Te films for phase change memory

Abstract: Crystallization process and amorphous state stability of Si-Sb-Te films with different Si concentration (10, 20 at. %) and Sb/Te ratio (2:3 and 1:1) have been studied and compared with Ge2Sb2Te5 (GST) film by in situ film resistance measurements. The effects of Si concentration and Sb content on crystalline resistivity, crystallization temperature, activation energy of crystallization, and amorphous state stability of films have been studied. The activation energy Ea of crystallization of GST film was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…2(d) and (e), high Zn-doping concentration increases the amorphous thermal stability of ZST4 and ZST5 films greatly, so we have to increase the annealing temperature to observe the drop of the sheet resistance. Generally speaking, the crystallization time decreases largely when the Sb/Te ratio increases [25]. The reason is that more Sb in Zn-Sb-Te films increases the crystallization rate of the films.…”
Section: Resultsmentioning
confidence: 95%
“…2(d) and (e), high Zn-doping concentration increases the amorphous thermal stability of ZST4 and ZST5 films greatly, so we have to increase the annealing temperature to observe the drop of the sheet resistance. Generally speaking, the crystallization time decreases largely when the Sb/Te ratio increases [25]. The reason is that more Sb in Zn-Sb-Te films increases the crystallization rate of the films.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 4 shows TEM image of the GST-TaO x ͑38.3 mol %͒ film after heating at 350°C for 5 min. Feng et al 22 reported that phase separate ͑Sb 2 Te 3 nanocrystals were surrounded by amorphous Si-rich grain boundaries͒ was found in annealed SiSbTe films. Lee et al 15 reported that separate domain formation ͑spherical Ge 2 Sb 2 Te 5 -rich domains were enclosed by SiO x -rich domains͒ was found in Ge 2 Sb 2 Te 5 -SiO x mixed layer.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some issues still need to be solved in PCRAM application. One of the most crucial issues is to reduce the power consumption in PCRAM devices, especially the consumption during the RESET process . Till now, many efforts such as realizing multilevel storage , inserting a heating layer , optimizing the structure of the PCM device , have been made to try to achieve these goals.…”
Section: Introductionmentioning
confidence: 99%